Decoding Gene Networks Modules That Explain the Recovery of Hymenoglossum cruentum Cav. After Extreme Desiccation - Ostria-Gallardo, Enrique; Larama, Giovanni; Berríos, Graciela; Fallard, Ana; Gutiérrez-Moraga, Ana; Ensminger, Ingo; Manque, Patricio; Bascuñán-Godoy, Luisa; Bravo, León A. (Frontiers in Plant Science, 2020)
Hymenoglossum cruentum (Hymenophyllaceae) is a poikilohydric, homoiochlorophyllous desiccation-tolerant (DT) epiphyte fern. It can undergo fast and frequent dehydration-rehydration cycles. This fern is highly abundant at high-humidity/low-light microenvironments within the canopy, although rapid changes in humidity and light intensity are frequent. The objective of this research is to identify genes associated to desiccation-rehydration cycle in the transcriptome of H. cruentum to better understand the genetic dynamics behind its desiccation tolerance mechanism. H. cruentum plants were subjected to a 7 days long desiccation-rehydration process and then used to identify key expressed genes associated to its capacity to dehydrate and rehydrate. The relative water content (RWC) and maximum quantum efficiency (Fv/Fm) of H. cruentum fronds decayed to 6% and 0.04, respectively, at the end of the desiccation stage. After re-watering, the fern showed a rapid recovery of RWC and Fv/Fm (ca. 73% and 0.8, respectively). Based on clustering and network analysis, our results reveal key genes, such as UBA/TS-N, DYNLL, and LHC, orchestrating intracellular motility and photosynthetic metabolism; strong balance between avoiding cell death and defense (CAT3, AP2/ERF) when dehydrated, and detoxifying pathways and stabilization of photosystems (GST, CAB2, and ELIP9) during rehydration. Here we provide novel insights into the genetic dynamics behind the desiccation tolerance mechanism of H. cruentum.